(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Asparagus racemosus Wild is an indigenous medicinal plant of family LILIACEAE. It is important for its sapogenim content, the precursor of many pharmacologically active steroids. It bears antioxidant activity and anti-abortifacient activity (shatvarin 1), antiviral activity, anticancer, antidysenteric activity. This species occurs widely throughout the tropical and subtropical regions of Indian subcontinent. The racemosides saponin content of its root revised the structures of two major saponins. Shatavarins 1,10 and IV,7.